2021
DOI: 10.1109/access.2021.3052051
|View full text |Cite
|
Sign up to set email alerts
|

Transactive Energy-Based Joint Optimization of Energy and Flexible Reserve for Integrated Electric-Heat Systems

Abstract: Implementing integrated electric-heat systems (IEHSs) with coupled power distribution networks and district heating networks is an essential means to solve current energy problems. However, prosumers with multiple energy forms coupled and renewable energy sources with natural uncertainties pose challenges to the operation of IEHSs. This paper proposes a joint energy and reserve dispatch model for IEHSs based on transactive energy, which is a coordinated combination of a bi-level Stackelberg game and two-stage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 31 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…For example, a nucleolus-based cooperative game solution is proposed in [317] that utilized the flexible loads of prosumers and considers the uncertainties of renewable energy resources to manage energy in local communities. A Stackelberg game is used to develop a joint energy and reserve dispatch model in [318] to ensure the reliability of system operation under renewable energy uncertainty. To maximize the benefit of distributed energy resources for flexible prosumers in terms of procuring revenues by trading electricity in the market, the authors in [319] and [320] explore algorithmic and non-cooperative games respectively to realize suitable transactive energy frameworks.…”
Section: B: Transactive Energymentioning
confidence: 99%
“…For example, a nucleolus-based cooperative game solution is proposed in [317] that utilized the flexible loads of prosumers and considers the uncertainties of renewable energy resources to manage energy in local communities. A Stackelberg game is used to develop a joint energy and reserve dispatch model in [318] to ensure the reliability of system operation under renewable energy uncertainty. To maximize the benefit of distributed energy resources for flexible prosumers in terms of procuring revenues by trading electricity in the market, the authors in [319] and [320] explore algorithmic and non-cooperative games respectively to realize suitable transactive energy frameworks.…”
Section: B: Transactive Energymentioning
confidence: 99%
“…The worst-case realization of the uncertainty of real-time electricity market prices was modeled in the second stage of an ARO in [1]. Finally, [94], [98] are the papers in this second category that use C&CG to deal with the uncertainties.…”
Section: ) Adaptive Robust Optimizationmentioning
confidence: 99%
“…The optimal bidding strategy of an EH considering the uncertainties from renewable energy resources, DA market price, and RT market price was modelled in [127]. The TEF for the scheduling and trading operations of coupled electric and thermal systems was discussed in [128][129][130]. Further research on the modelling of P2P energy trading among EHs can be found in [131,132].…”
Section: E Lossmentioning
confidence: 99%